2007
DOI: 10.1109/tim.2007.900126
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Tree-Foliage Surface Estimation Using a Ground Laser Scanner

Abstract: Abstract-The optimization of most pesticide and fertilizer applications is based on overall grove conditions. In this paper, we propose a measurement system to estimate the foliage surface of a tree crop. The system is based on a ground laser scanner that estimates the volume of the trees and then extrapolates their leaf area using simple and fast algorithms to allow true real-time operation. Tests with pear trees demonstrated that the relation between the volume and the foliage can be interpreted as linear wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 15 publications
0
45
0
Order By: Relevance
“…Another possibility is the use of ground-based sensors to get information about the geometry and/or structure of the canopy (López-Lozano et al 2009;Rosell et al 2009b;Llorens et al 2011). Specifically, laser sensors have been tested in fruit orchards (apple and pear) (Walklate et al 2002;Palacín et al 2007;Rosell et al 2009a;Sanz et al 2011), in citrus (Wei and Salyani 2004;Lee and Ehsani 2009) and in grapevine, in which in addition to laser sensors (Arnó et al 2006;Rosell et al 2009b;Llorens et al 2011), radiometric sensors mounted on tractors were used (Goutouly et al 2006;Drissi et al 2009;Mazzetto et al 2010). As an alternative to optical sensors, ultrasonic sensors (US) have been used to estimate LAI in cereals (Scotford and Miller 2004) and measure canopy volume in different crops: fruit trees (Giles et al 1988;Solanelles et al 2006;Escolà et al 2011), grapevines (Gil et al 2007;Llorens et al 2011) and citrus (Tumbo et al 2002;Schumann and Zaman 2005;Zaman and Schumann 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is the use of ground-based sensors to get information about the geometry and/or structure of the canopy (López-Lozano et al 2009;Rosell et al 2009b;Llorens et al 2011). Specifically, laser sensors have been tested in fruit orchards (apple and pear) (Walklate et al 2002;Palacín et al 2007;Rosell et al 2009a;Sanz et al 2011), in citrus (Wei and Salyani 2004;Lee and Ehsani 2009) and in grapevine, in which in addition to laser sensors (Arnó et al 2006;Rosell et al 2009b;Llorens et al 2011), radiometric sensors mounted on tractors were used (Goutouly et al 2006;Drissi et al 2009;Mazzetto et al 2010). As an alternative to optical sensors, ultrasonic sensors (US) have been used to estimate LAI in cereals (Scotford and Miller 2004) and measure canopy volume in different crops: fruit trees (Giles et al 1988;Solanelles et al 2006;Escolà et al 2011), grapevines (Gil et al 2007;Llorens et al 2011) and citrus (Tumbo et al 2002;Schumann and Zaman 2005;Zaman and Schumann 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, high efficiency and low production costs can be achieved for pesticide spray applications with minimum environmental impact [7,8,9,10,11,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Laser scanners mounted onto various mobile terrestrial platforms have been increasingly described these years, and the subject of tree properties investigation based on mobile laser scanning (MLS) has been increasingly exploited. The associated application cases involve individual tree recognition [22], assessment of the influence of foliation on laser pulse echoes [23], real-time tree-foliage surface estimation [24], multi-echoes-based crown reconstruction [25], etc. As regards mobile hyperspectral imaging, its implementation tends to be concisely mentioned in the specs of mobile mapping systems [20], and little research on tree spectral reflectance properties has been reported.…”
Section: Introductionmentioning
confidence: 99%